Analisis Differensiasi Produk dan Citra Merek terhadap Keputusan Pembelian Konsumen pada Sepeda Motor Merek Yamaha Mio di Kota Langsa - Maulana Rahman; Nawa Suhayani (Universitas Samudra, 2020)
This study aims to analyze product differentiation and brand image on the customer purchase decision, with a case study of the Yamaha Mio brand of matic-bike in Langsa City. Multiple regression method was used to analyze data.. The results showed that partially, product differentiation and brand image had a positive and significant influence on consumer purchasing decisions. Simultaneously, the two independent variables were also obtained to have a significant influence on dependent variable. Thus, if the company implements strategies related to product differentiation and brand image, partially or simultaneously, it will strengthen the purchasing decisions made by consumers for products offered. However, the determination analysis identifies that there are several main factors that are considered to influence consumer purchasing decisions but are not included in this research model.